Pedagogical The Essential Essence Of Using The Hadiths Of Imam Al-Bukhary In The Teaching Of Psychological Sciences - Dzhiyanberdiyev Merojiddin Egamberdi Ogli (Academia One, 2024)
This article, One of the urgent problems of the present time is the study and analysis of our national values, the improvement of relations between people living in society for the development of society , the essence of using Imam al-Bukhari's hadiths in the teaching of pedagogical psychology. focused on issues
Keywords: Pedagogical psychology; national value; universal value; hadith